Report about HPAI introduction into Europe, HPAI detection in wild birds and HPAI spread between European holdings in the period 2005‐2015. Issue 10 (16th October 2017) - ,; ,; ,; ,; ,; ,; Duncan, Daisy; Harris, Kate; Poen, Marjolein; Kowalezyk, Stefan; Fouchier, Ron; Staubach, Christoph; et al.
Abstract : This publication is linked to the following EFSA Journal article:http://onlinelibrary.wiley.com/doi/10.2903/j.efsa.2017.4991/full, http://onlinelibrary.wiley.com/doi/10.2903/j.efsa.2017.5018/full This publication is linked to the following EFSA Supporting Publications article:http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2017.EN-1282/full, http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2017.EN-1283/full, http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2017.EN-1285/full, http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2017.EN-1286/full, http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2017.EN-1287/full